ANALISIS RISIKO ERGONOMI PENJAHIT BERDASARKAN JENIS KELAMIN DI KOTA BATAM - Laia, Capai; Zetli, Sri (Computer Science and Industrial Engineering, 2023)
The development of the fashion sector in today's modern world is undoubtedly quite promising. Many entrepreneurs start industrial businesses in the clothing sector or what is often referred to as the garment industry, because the need for clothing production is very large. As a result of the very promising profits from the clothing business, many large, medium and small informal companies have flocked to open this business. As a profit-oriented company, on the other hand it also generates many health problems and increases the likelihood of workplace accidents. This is because there are many possible risks in the workplace, including chemical, physical, biological, ergonomic, as well as psychosocial hazards, all of which have an impact on the health of workers